Enhancement in Photoelectrochemical Performance of Optimized Amorphous SnS2 Thin Film Fabricated through Atomic Layer Deposition - Weiguang Hu; Truong Thi Hien; Dojin Kim; Hyo Sik Chang (Nanomaterials, 2019)
Two-dimensional (2D) nanomaterials have distinct optical and electrical properties owing to their unique structures. In this study, smooth 2D amorphous tin disulfide (SnS2) films were fabricated by atomic layer deposition (ALD), and applied for the first time to photoelectrochemical water splitting. The optimal stable photocurrent density of the 50-nm-thick amorphous SnS2 film fabricated at 140 °C was 51.5 µA/cm2 at an oxygen evolution reaction (0.8 V vs. saturated calomel electrode (SCE)). This value is better than those of most polycrystalline SnS2 films reported in recent years. These results are attributed mainly to adjustable optical band gap in the range of 2.80 to 2.52 eV, precise control of the film thickness at the nanoscale, and the close contact between the prepared SnS2 film and substrate. Subsequently, the photoelectron separation mechanisms of the amorphous, monocrystalline, and polycrystalline SnS2 films are discussed. Considering above advantages, the ALD amorphous SnS2 film can be designed and fabricated according to the application requirements.